2021
DOI: 10.12688/f1000research.72937.1
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic knowledge and practices of milk vending machine handlers in the informal settlements of Nairobi, Kenya

Abstract: Background: Poor milk handling practices due to lack of knowledge or deliberate adulteration compromises the safety of milk and that of the consumer. With the increase of milk vending machines in informal settlements, the knowledge and practices of vendors concerning milk hygiene are critical in determining milk safety. The operation of milk vending machines is guided by strict regulations that aim at ensuring proper practices among milk handlers, but the level of implementation among milk vendors is questiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This result aligns with investigation by Pratiwi et al (2016), who reported that most cow farmers in Cipageran Village, North Cimahi District, Cimahi City, had sufficient knowledge (66.67%). Learning can be influenced by a person's level of education and age (Kevin et al, 2021). Education encourages a person to obtain more information to understand something better.…”
Section: Distribution Of Farmers' Knowledgementioning
confidence: 99%
“…This result aligns with investigation by Pratiwi et al (2016), who reported that most cow farmers in Cipageran Village, North Cimahi District, Cimahi City, had sufficient knowledge (66.67%). Learning can be influenced by a person's level of education and age (Kevin et al, 2021). Education encourages a person to obtain more information to understand something better.…”
Section: Distribution Of Farmers' Knowledgementioning
confidence: 99%